2010
DOI: 10.1189/jlb.1009659
|View full text |Cite
|
Sign up to set email alerts
|

A role for STAT3 and cathepsin S in IL-10 down-regulation of IFN-γ-induced MHC class II molecule on primary human blood macrophages

Abstract: IL-10, a potent anti-inflammatory cytokine, activates its primary mediator STAT3 to exert inhibitory effects on activated immune response. It has been reported that IFN-gamma signaling can be suppressed by IL-10, which deactivates macrophages and suppresses cell-mediated antigen presentation. Cathepsin S, a cysteine protease, plays a significant role in the antigen processing. We hypothesize that the IL-10-induced and STAT3-mediated signaling pathway interferes with IFN-gamma-induced immune responses in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 60 publications
2
42
0
1
Order By: Relevance
“…Binding of IFN γ to its receptor activates STAT-1, which in turn binds to transcription factors that will stimulate MHC-II, protein kinase (PKR), and ribonuclease L expression. Thus, blocking or failure of the IFN γ signaling pathway confers higher susceptibility to infections, suggesting that secretion of IFN γ may be an important effector function for the suppression of HIV-1 and other viral infections [3133]. In this study, the IFN γ +874TT genotype, which is associated with high IFN γ production, was related to considerably higher levels of CD4+ T lymphocytes compared to the other two genotypes (AA and AT).…”
Section: Discussionmentioning
confidence: 56%
“…Binding of IFN γ to its receptor activates STAT-1, which in turn binds to transcription factors that will stimulate MHC-II, protein kinase (PKR), and ribonuclease L expression. Thus, blocking or failure of the IFN γ signaling pathway confers higher susceptibility to infections, suggesting that secretion of IFN γ may be an important effector function for the suppression of HIV-1 and other viral infections [3133]. In this study, the IFN γ +874TT genotype, which is associated with high IFN γ production, was related to considerably higher levels of CD4+ T lymphocytes compared to the other two genotypes (AA and AT).…”
Section: Discussionmentioning
confidence: 56%
“…This might occur through LIF-induced activation of STAT3 that could exert a negative control, directly or indirectly, by acting in proximal or distal transcriptional activators of the hCG genes. In accordance with this proposed mechanism, a recent study has demonstrated that the inhibitory effects of IL10 on the antigen-presenting capacity of interferon c (IFNG)-stimulated human macrophages may act, via STAT3, by a negative transcriptional regulation of cathepsin S and major histocompatibility complex (MHC) II genes [50]. Therefore, a detailed promoter analysis would be required to explore whether STAT3, and even STAT1 or STAT1-STAT3 heterodimers, plays a role in mediating the inhibitory action of LIF on the promoters of hCG gene and an opposed positive action of LIF on fusion-related gene promoters.…”
Section: Leduc Et Almentioning
confidence: 72%
“…It is possible that STAT3 may play a major role in this effect since many cytokines produced by tumors one way or another may trigger STAT3 signaling in myeloid cells and up-regulation of STAT3 is a common finding in myeloid cells in TB hosts (3436). On the other hand, it is known that up-regulation of STAT3 results in reduction of MHC class II expression in DCs (17, 37, 38). …”
Section: Discussionmentioning
confidence: 99%